2006
DOI: 10.1021/bi060142r
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Photocontrol of DNA Binding by a Designed GCN4-bZIP Protein

Abstract: Synthetic photocontrolled proteins could be powerful tools for probing cellular chemistry. Several previous attempts to produce such systems by incorporating photoisomerizable chromophores into biomolecules have led to photocontrol but with incomplete reversibility, where the chromophore becomes trapped in one photoisomeric state. We report here the design of a modified GCN4-bZIP DNA-binding protein with an azobenzene chromophore introduced between Cys residues at positions 262 and 269 (S262C, N269C) within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 57 publications
0
73
0
Order By: Relevance
“…They showed that adding the missing helix could constitute the trimer, and with it the enzyme [30]. Reversible photo-activation of coiled-coil transcription factor binding to DNA has also been demonstrated [31]. These applications illustrate the potential utility of coiled coils for biomedical or materials applications, which will be enhanced as we understand sequencestructure relationships better.…”
Section: Novel Structures Switches and Functionsmentioning
confidence: 93%
“…They showed that adding the missing helix could constitute the trimer, and with it the enzyme [30]. Reversible photo-activation of coiled-coil transcription factor binding to DNA has also been demonstrated [31]. These applications illustrate the potential utility of coiled coils for biomedical or materials applications, which will be enhanced as we understand sequencestructure relationships better.…”
Section: Novel Structures Switches and Functionsmentioning
confidence: 93%
“…A variety of helical peptides and proteins bearing two Cys residues have been cross-linked, and their conformational and functional properties have been studied; these include the peptides JRK-7 and FK-11 and the proteins MyoD, engrailed and GCN4 27,[29][30][31] . Intermolecular cross-linking between proteins was not apparent in any of these cases and was likely suppressed by the fast intramolecular reaction between the chloroacetamide moiety of BSBCA and the second Cys residue.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly relevant are those based on dimeric bZIP basic regions, in which the natural C/C-terminal leucine zipper is replaced by artificial dimerizers [14][15][16][17] . Some of these designs have gone even further and incorporate switchable elements that allow conditional off/on DNA binding by the application of external stimuli such as light or metal ions [18][19][20][21][22] . Despite advances in these and other switchable DNA binders 23,24 , designed systems capable of interacting with alternative DNA sites in an externally regulated manner are unknown.…”
mentioning
confidence: 99%